2015
DOI: 10.1016/j.ijfatigue.2015.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue crack initiation behaviors throughout friction stir welded joints in AA7075-T6 in ultrasonic fatigue

Abstract: This paper presents the results of experimental investigation on fatigue behaviors of friction stir welded joints in AA7075-T6 with ultrasonic fatigue test system (20 kHz). Two kinds of particles, Fe-rich intermetallic compounds and Mg 2 Si-based particles, governed the fatigue crack initiation. The plastic deformation and recrystallization during welding process led to the changes in particle size and micro crack occurrence between thermo-mechanically affected zone (TMAZ) and nugget zone (NZ). Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The fatigue strength of peened specimens decreased continuously with the increasing fatigue life up to the VHCF range, while the S–N curve of un‐peened specimen exhibited a horizontal platform within the range of 10 7 –10 8 cycles. It has been found that the platform corresponded to the transition duration of fatigue crack initiation sites from the TMAZ in short fatigue life to the NZ in the VHCF . The monotonically decreasing fatigue resistance for peened specimen probably implies a different failure mechanism as compared with un‐peened specimen, and this will be explained in the following sections.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…The fatigue strength of peened specimens decreased continuously with the increasing fatigue life up to the VHCF range, while the S–N curve of un‐peened specimen exhibited a horizontal platform within the range of 10 7 –10 8 cycles. It has been found that the platform corresponded to the transition duration of fatigue crack initiation sites from the TMAZ in short fatigue life to the NZ in the VHCF . The monotonically decreasing fatigue resistance for peened specimen probably implies a different failure mechanism as compared with un‐peened specimen, and this will be explained in the following sections.…”
Section: Resultssupporting
confidence: 50%
“…The fatigue crack initiation behaviours of un‐peened FSW joint have been investigated in our previous work . It was found that fatigue crack originated from the TMAZ on the advancing side in high cycle fatigue range, because the interior particles were cracked under the intense plastic deformation during the FSW process, and fatigue cracks started propagating directly from these pre‐existing microcracks under the cyclic loading.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It revealed that the fatigue crack originated at the advancing side due to the effects of microstructural heterogeneity. Our previous work [12,13] also found that fatigue crack initiation sites were localized at the thermomechanically affected zone on the advancing side below 10 8 cycles. Nevertheless, the failure was prone to occur at the nugget zone in the VHCF regime.…”
Section: Introductionmentioning
confidence: 79%
“…For comparison, the data of AA 7075 FSW joint obtained from the full specimen in our previous work are also presented [13], in which the fatigue failures occurred at the TMAZ in high cycle fatigue regime and at the NZ in the VHCF. It is clear that the fatigue strength keeps going down with cyclic load increasing.…”
Section: S-n Curvesmentioning
confidence: 99%